2001
DOI: 10.1007/s005860000223
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cancellous bone density on load sharing in human lumbar spine: a comparison between an intact and a surgically altered motion segment

Abstract: IntroductionLittle is known about the exact distribution of forces within healthy lumbar spine due to its complex geometry and physiology. Furthermore, defects by trauma or tumorous destruction may influence spinal biomechanics to a great extent. Surgery also changes the biomechanics of the spine, and the true way in which the spine behaves following, for instance, decompression and stabilisation can only be estimated.Loads applied onto the spine are shared among spinal components: this is called spinal load s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 23 publications
(52 reference statements)
0
19
0
1
Order By: Relevance
“…The thickness of the lateral cortical wall was 0.35 mm and the thickness of the vertebral endplates was 0.5 mm (Silva et al, 1994). It has been shown that the center of the vertebral endplates is weaker and less stiff Baroud et al (2003), Goel et al (1995), Homminga et al (2002), Pitzen et al (2001), Shirazi-Adl et al (1984) Hexahedral Cancellous bone 100 0.2 Dooris et al (2001), Goel et al (1993), Lavaste et al (1992), Linde (1994), Sharma et al (1995), Shirazi-Adl et al (1984) Tetrahedral Posterior vertebra 3000 0.3 Smit et al (1997) Hexahedral Annulus ground substance 4.2 0.45 Goel et al (1993Goel et al ( , 1995, Pitzen et al (2001), Sharma et al (1995), Shirazi-Adl et al Goel et al (1993Goel et al ( , 1995, Pitzen et al (2001), Sharma et al (1995), Smit et al (1997) Hexahedral (Grant et al, 2001;Polikeit et al, 2003). As a consequence, the endplates were partitioned into three areas with variable mechanical characteristics ranging from 2000 to 12,000 MPa as shown in Fig.…”
Section: Healthy Modelmentioning
confidence: 97%
See 2 more Smart Citations
“…The thickness of the lateral cortical wall was 0.35 mm and the thickness of the vertebral endplates was 0.5 mm (Silva et al, 1994). It has been shown that the center of the vertebral endplates is weaker and less stiff Baroud et al (2003), Goel et al (1995), Homminga et al (2002), Pitzen et al (2001), Shirazi-Adl et al (1984) Hexahedral Cancellous bone 100 0.2 Dooris et al (2001), Goel et al (1993), Lavaste et al (1992), Linde (1994), Sharma et al (1995), Shirazi-Adl et al (1984) Tetrahedral Posterior vertebra 3000 0.3 Smit et al (1997) Hexahedral Annulus ground substance 4.2 0.45 Goel et al (1993Goel et al ( , 1995, Pitzen et al (2001), Sharma et al (1995), Shirazi-Adl et al Goel et al (1993Goel et al ( , 1995, Pitzen et al (2001), Sharma et al (1995), Smit et al (1997) Hexahedral (Grant et al, 2001;Polikeit et al, 2003). As a consequence, the endplates were partitioned into three areas with variable mechanical characteristics ranging from 2000 to 12,000 MPa as shown in Fig.…”
Section: Healthy Modelmentioning
confidence: 97%
“…A natural ligament exhibits strong nonlinear load/deformation behavior (White and Panjabi, 1990). As with most of the reported FEM studies (Dooris et al, 2001;Goel et al, 1993Goel et al, , 1995Pitzen et al, 2001;Smit et al, 1997), the current model has adopted a bilinear model, described in Table 2.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known from previous studies that ceramic material sometimes has tends to fracture, however, with no reported change in the position of the treated segment [9,60]. It is also known from the literature that the average elasticity module of the lumbar cancellous bone of a 60-year old individual is about 25 MPa [46]. The required compressive strength of the bone substitute of 30 MPa was thus judged sufficient for the size of the blocks tested in order to avoid fractures during testing.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have analytically examined spinal segments using the finite element method Lavaste et al, 1992;Pitzen et al, 2001;Shirazi-Adl, 1991;Zander et al, 2001Zander et al, , 2002. To calculate intersegmental rotation as well as stresses and strains in their components, this method requires data on the geometry, loads, and material properties of the different components.…”
Section: Introductionmentioning
confidence: 99%